Optimasi Hasil Ubikayu Menggunakan Teknologi Adaptif - Budhi Santoso Radjit; Nila Prasetiaswati (Iptek Tanaman Pangan, 2011)
Cassava is an alternative crop for food and for energy, due to its high productivity. Of the harvested area of about 1.2 million ha, the national average yield of cassava is only about 18 t/ha, with the highest productivity of 24.6 t/ha obtained from Lampung Province. The high need for food and industrial raw materials for domestic and export, requires for identifying technologies that can increase productivity of cassava. Based on studies conducted in Malang, Banyuwangi, South Lampung, and Central Lampung, the application of proper crop management was able to increase yields. In southern Malang, used input of 10 t/ha manure, 300 kg/ha urea and 300 kg Phonska/ha on varieties Cecek Hijau, Sembung, and Malang-6 was able to obtain fresh tuber yield between 80-87 t/ha with a profit between Rp 37,610,000/ha to Rp 41,810,000/ha. In KP Genteng, Banyuwangi district, applying fertilizers at rate of 300 kg/ha urea, 100 kg/ha of SP36, 100 kg/ha of KCl and 5 t/ha manure, produced fresh tuber yield between 54-62 t/ha with a profit between Rp 19-23 million/ha, and B/C ratio between 2.5 to 3.0. In Natar (South Lampung) and Sulusuban (Central Lampung), applying 300 kg urea/ha, 200 kg SP36/ha, 200 kg KCl/ha, and 500 kg dolomite/ha, plus 5 t manure/ha produced between 46-60 t/ha of fresh tubers with Rp 26 to Rp 31 million profit. The apparent high yields and profits from cassava farming were obtained from the application of high inputs in combination with deep soil tillage. Reasonable good cassava price ranged between Rp 550-650/kg, had contributed to high profit earned by farmers. Although cassava yield obtained from the use of high input seems quite profitable, however its adoption and its yield sustainability need to be studied further, mainly relates to sustainable soil fertility. Price stability for fresh tubers, inorganic fertilizers and manure availability, and access to capital, need to be supported by the local government in order that farmers adopt the technology.